Clinical importance of muscle volume in lenvatinib treatment for hepatocellular carcinoma: Analysis adjusted with inverse probability weighting. Issue 7 (29th November 2020) - Hiraoka, Atsushi; Kumada, Takashi; Kariyama, Kazuya; Tada, Toshifumi; Tani, Joji; Fukunishi, Shinya; Atsukawa, Masanori; Hirooka, Masashi; Tsuji, Kunihiko; Ishikawa, Toru; Takaguchi, Koichi; Itobayashi, Ei; et al.
Abstract: Background and Aim: This study aimed to elucidate the clinical importance of muscle volume loss (pre‐sarcopenia) in patients receiving lenvatinib as treatment for unresectable hepatocellular carcinoma (u‐HCC). Methods: Of 437 u‐HCC patients treated with lenvatinib at specific institutions in Japan between March 2018 and May 2020, 151 with available computed tomography imaging data from the time of lenvatinib introduction were enrolled. Pre‐sarcopenia was diagnosed based on a previously reported cut‐off value calculation formula [psoas muscle area at level of middle of third lumbar vertebra (cm 2 )/height (m) 2 ]. Clinical features and prognostic factors for overall survival (OS) with inverse probability weighting were investigated retrospectively for their relationship with pre‐sarcopenia. Results: Cox hazard multivariate analysis showed alpha‐fetoprotein (≥400 ng/mL) (hazard ratio [HR] 2.271, P < 0.001), Barcelona Clinic Liver Cancer stage (C and D) (HR 1.625, P = 0.018), and positive for pre‐sarcopenia (HR 1.652, P = 0.042) to be significant prognostic factors. OS rates for the pre‐sarcopenia group ( n = 41) were worse than those for the non‐pre‐sarcopenia group ( n = 110) (0.5‐, 1‐, and 1.5‐year OS: 72.5%, 27.9%, and 7.0% vs 80.7%, 56.7%, and 46.1%, respectively; P < 0.001), as was progression‐free survival ( P = 0.025). Time to stopping lenvatinib or disease progression was better in the non‐pre‐sarcopenia group (0.5‐, 1‐, and 1.5‐year OS: 48.0%, 24.5%, and 8.4% vs 20.0%, 10.3%, and 4.2%, respectively; P < 0.001). Also, the frequency of the adverse event appetite loss (any grade) was greater in the pre‐sarcopenia group (43.9% vs 18.2%, P = 0.003). Conclusion: Pre‐sarcopenia was shown to be a significant prognostic factor in patients treated with lenvatinib for u‐HCC.